2007
DOI: 10.1007/s10725-007-9217-8
|View full text |Cite
|
Sign up to set email alerts
|

Sea fennel (Crithmum maritimum L.) under salinity conditions: a comparison of leaf and root antioxidant responses

Abstract: The present study was carried out to compare the effect of NaCl on growth, cell membrane damage, and antioxidant defences in the halophyte Crithmum maritimum L. (sea fennel). Physiological and biochemical changes were investigated under control (0 mM NaCl) and saline conditions (100 and 300 mM NaCl). Biomass and growth of roots were more sensitive to NaCl than leaves. Roots were distinguished from leaves by increased electrolyte leakage and high malondialdehyde (MDA) concentration. Superoxide dismutas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 63 publications
(68 reference statements)
5
57
0
2
Order By: Relevance
“…The electrolyte leakage (EL) was determined as described by Ben Hamed et al (2007) in leaves' tissue of the coriander plants. The level of lipid peroxidation in coriander leaves was determined as the amount of 2-thiobarbituric acidreactive substances (TBARS) by means of malondialdehyde (MDA) and other aldehydes content formed as described by Heath and Packer (1968) and Meirs et al (1992), respectively.…”
Section: Electrolyte Leakage Mda and H 2 O 2 Assaymentioning
confidence: 99%
“…The electrolyte leakage (EL) was determined as described by Ben Hamed et al (2007) in leaves' tissue of the coriander plants. The level of lipid peroxidation in coriander leaves was determined as the amount of 2-thiobarbituric acidreactive substances (TBARS) by means of malondialdehyde (MDA) and other aldehydes content formed as described by Heath and Packer (1968) and Meirs et al (1992), respectively.…”
Section: Electrolyte Leakage Mda and H 2 O 2 Assaymentioning
confidence: 99%
“…For the calculation of MDA and other aldehydes, it was used the extinction coefficients (e) 1.55 x 10 , respectively. The electrolyte leakage (EL) was determined as described by Ben Hamed et al (2007). The plant samples (300 mg of FW) were placed in plastic test tubes containing 15 mL of ultra-pure water.…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…This robust antioxidant activity is considered to be effective in protecting mangroves from excess irradiance (which generates ROS) under natural conditions (Cheeseman et al, 1997). Higher antioxidant defences in leaves compared to those of roots accounted for the survival of the halophyte Crithmum maritimum L. under high salinity conditions (Ben Hamed et al, 2007). In the same species, Ben Amor et al (2005) showed an increased total SOD activity in shoot tissues in presence of 50 mM NaCl stress while SOD activity in root tissues decreased upon salt treatment (up to 200 mM).…”
Section: Introductionmentioning
confidence: 99%